Burden of Crohn's disease in the United States: long-term healthcare and work-loss related costs. (2nd October 2020) - Manceur, Ameur M.; Ding, Zhijie; Muser, Erik; Obando, Camilo; Voelker, Jennifer; Pilon, Dominic; Kinkead, Frederic; Lafeuille, Marie-Hélène; Lefebvre, Patrick
Abstract: Aims: To quantify the long-term direct and indirect costs among patients with Crohn's disease (CD) and specific subgroups of these patients in the United States from the private payer's perspective. Materials and methods: This retrospective study used the OptumHealth Care Solutions, Inc database (01 January 1999–31 March 2017) to match (1:5) adult patients with ≥2 claims for CD to patients without inflammatory bowel disease (IBD). Patterns observed during follow-up (i.e. biologics, opioids, or steroids; CD-related surgery; moderate-to-severe disease; and comorbidities) were used to identify CD subgroups. Comparisons of healthcare resource utilization, work loss days, and direct and indirect work loss-related costs were made between matched cohorts. Descriptive analyses of costs were conducted within each CD subgroup. Results: There were 6, 715 and 33, 575 patients in the CD and non-IBD cohorts, respectively. The direct burden was significantly higher in the CD cohort compared to the non-IBD cohort, with 0.34 inpatient admissions per patient per year (PPPY) versus 0.12 (217% increase; p < .001), and 24, 500 direct healthcare costs PPPY versus 7, 037 (17, 463 increase; p < .001). The trend was similar for the indirect burden, with work loss–related costs PPPY of 5, 490 in the CD cohort versus 3, 322 in the non-IBD cohort (2, 168 increase; p < .001). The burden was numerically higher in the CD subgroups, with direct healthcare costs reaching 101, 013 PPPY in the surgery subgroup. Limitations: Severity of CD was determined based on claims-based algorithms due to the lack of access to medical files. Absenteeism was imputed based on claims data, and presenteeism was not assessed. Conclusions: The direct healthcare and indirect work loss–related costs of patients with CD was significantly higher compared to patients without IBD over an average follow-up of 5 years.